Effect of two mouthwashes on salivary PH - Belardinelli, P. A. (2004)
To analyze the effect of two mouthwashes on salivary pH and correlate it with age, buffer capacity and saliva flow rate in healthy volunteers, a crossover phase IV clinical study involving three age-based groups was designed. Two commercial mouthwashes (MW), Cool Mint Listerine® (MWa) and Periobacter ® (MWb) were used. The unstimulated saliva of each individual was first characterized by measuring flow rate, pH, and buffer capacity. Salivary pH was evaluated before rinsing with a given MW, immediately after rinsing, 5 minutes later, and then every 10 min (at 15, 25, 35 min) until the baseline pH was recovered. Paired t-test, ANOVA with a randomized block design, and Pearson correlation tests were used. Averages were 0.63 mL/min, 7.06, and 0.87 for flow rate, pH, and buffer capacity, respectively. An immediate significant increase in salivary pH was observed after rinsing, reaching average values of 7.24(MWb) and 7.30 (MWa), which declined to an almost stable value 15minutes. The great increase in salivary pH, after MW use shows that saliva is a dynamic system, and that the organism is capable of responding to a stimulus with changes in its composition. It is thus evident that pH of the external agent alone is not a good indicator for its erosive potential because biological systems tend to neutralize it. The results of this study enhance the importance of in vivo measurements and reinforce the concept of the protective action of saliva.